(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Group B streptococci (GBS) are globally recognized to cause adverse pregnancy outcomes, such as stillbirths and miscarriages, and are one of the main causes of newborn sepsis and meningitis. The high resistance of GBS to antibiotics becomes difficult or impossible to treat, becoming increasingly common, causing a global health crisis. It complicates their eradication, potentially leading to the development of chronic infections. A total of 181 specimens were obtained from pregnant women. Out of these specimens, 22 isolates were bacteriologically identified as S.agalactiae. They were collected from Al-Anbar Province hospitals. Twenty-two isolates were identified as GBS depending on cultural and microscopical properties, automated (VITEK-2 system), and molecular identification based on atr gene, which is an essential gene expressed isolates in all S.agalactiae. The antimicrobial susceptibility test was done by using the disc diffusion method for(12) antimicrobials. The results was appeared the highest resistance to Erythromycin (100%), Cefotaxime (100%), Ceftriaxone (100%), Meropenem(100%), Tetracyclin (95.45%), Cefepime (90.90%), Ampicillin (90.90%), Penicillin (86.36%), Clindamycin(81.81%), Azithromycin (81.81%), Chloramphenicol (40.90%), Levofloxacin (22.72%). Biofilm formation estimation by using a microtiter plate (MTP) was performed. Out of 22 isolates of S.agalactiae, 20(90.90%)isolates produced biofilm as indicated by MtP. Out of 20 biofilm-producing isolates, 3(15%), 10(50%), and 7(35%)were weak, moderate, and strong, respectively. The inhibitory effects of Gallic acid, Cinnamic acid, Salicin, (-)-Epigallocatechingallate, Linoleic acid, Metronidazole, Amoxicillin, Erythromycin, and Levofloxacin were tested against biofilms of streptococcus agalactiae from pregnant women. The salicin was found to have strong bactericidal activity against biofilm. Inhibition of biofilm formation and growth after incubation with different concentrations of phytochemical compounds and antibiotics solution were assessed by the crystal violet and 3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide reduction assay. The phytochemical compounds and antibiotics solution significantly inhibited the initial cell attachment of the GBS but were less inhibitory towards 8 h preformed biofilms formed on polystyrene surface except for erythromycin; the inhibition was very low because of the resistance of GBS to erythromycin. However, there was a synergistic effect between erythromycin and gallic acid,or Metronidazole by using Checkerboard technique.